Islamic Republic of Pakistan : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The objective of the CFAA is to enhance knowledge of public financial management (PFM) and accountability arrangements in Bank's client countries. As a diagnostic tool, the CFAA supports the Bank's fiduciary responsibilities by identifying strengths and weaknesses of PFM so that potential risks to Bank funds can be managed. It also supports the Bank's development objectives by facilitating common understanding with the borrower and other development partners to assist in the design of PFM capacity building programs. The CFAA can also be used by the Government of Pakistan (GoP) to manage its internal finances and to strengthen accountability frameworks. This Country Financial Accountability Assessment concludes that there are substantial opportunities for consolidating current reforms and for introducing additional reforms to further strengthen public financial accountability. This will require sustained policy level commitment. The Government's will to reform is evidenced by the scale and variety of actions underway at the Federal and provincial levels. The Government of Pakistan has already embarked upon wide ranging reforms to improve budgetary and accounting systems and internal control arrangements. These reforms are now starting to show results: The risks of revenue shortfalls have been reduced with the initiation of tax policy and tax administration reforms ~ The risks of increasing excess debt have been reduced by more controlled budgeting and debt management though the use of the Medium-Term Budget Framework (MTBF) and the establishment of the Debt Office The risks of late and inaccurate federal annual accounts have been reduced by improved accounting controls introduced by the Controller General of Accounts (CGA) in compilation of accounts and the Fiscal Monitoring Committees in encouraging reconciliations. The risks of limited transparency in accounts at all levels have been reduced by the decisions to give the Auditor General responsibility for certification audit of all annual government accounts.